2011
DOI: 10.4314/ijhr.v3i2.70270
|View full text |Cite
|
Sign up to set email alerts
|

Maternal BMI during Pregnancy: Effect on trace elements Status and Pregnancy Outcomes

Abstract: and full-text of published articles. The journal is devoted to the promotion of health sciences and related disciplines (including medicine, pharmacy, nursing, biotechnology, cell and molecular biology, and related engineering fields). It seeks particularly (but not exclusively) to encourage multidisciplinary research and collaboration among scientists, the industry and the healthcare professionals. It will also provide an international forum for the communication and evaluation of data, methods and findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 38 publications
1
26
1
2
Order By: Relevance
“…There is a direct relationship between older aged women and obesity in this study. This corroborate with findings from other studies 9,11,24 but contrary to what was reported elsewhere 7,8,20 . This may reflect physiological changes associated with increased adiposity with increasing age and more so older women are more likely to be parous, with weight gain during previous pregnancies cumulatively predisposing them to obesity.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…There is a direct relationship between older aged women and obesity in this study. This corroborate with findings from other studies 9,11,24 but contrary to what was reported elsewhere 7,8,20 . This may reflect physiological changes associated with increased adiposity with increasing age and more so older women are more likely to be parous, with weight gain during previous pregnancies cumulatively predisposing them to obesity.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of obesity among early booked pregnant women found in this study is however higher than the reported range of obesity among pregnant women of 1.8 -25.3% quoted by WHO 4 . Surprisingly, the value from our study is also about three times the reported rates of 7.4 -10.7% from other regions of the country 8,14,15 , but a high rate of 22.6% has also been reported from Abakaliki, Southeastern Nigeria 9 .…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Included studies were from Nigeria ( n = 16), South Africa ( n = 7), Egypt ( n = 2), Ghana ( n = 1), Tanzania ( n = 1), Zimbabwe ( n = 1) and a final study conducted in seven African countries. With respect to quality, 11 studies were weak, 46 , 48 , 51 , 56 , 57 , 59 , 62 , 63 , 65 , 69 , 72 12 moderate 50 , 52 , 54 , 55 , 60 , 61 , 64 , 66 , 67 , 68 , 71 , 73 and 6 studies were classified as strong. 47 , 49 , 58 , 70 , 74 , 75 Most studies gave weak descriptions about controlling for confounders and/or about data collection methods.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…The authors have also reported a positive relationship of maternal BMI with age, parity and socioeconomic status among pregnant Nigerians 32 This may have important public health implications as adverse pregnancy outcomes have been associated with multiparity and increased maternal BMI [33][34][35] . It may be argued that the higher incidence of some pregnancy complications in high parous women, such as preterm delivery and macrosomia 36,37 may be related to increase in maternal BMI.…”
Section: Singh Et Almentioning
confidence: 78%